2015
DOI: 10.1007/s10803-015-2445-2
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Association of Autistic Traits and Behavioural Patterns in Adolescents Receiving Special Educational Assistance

Abstract: Those with PDD or autism display significantly higher levels of withdrawal, somatic complaints, anxiety/depression, social, thought and attention problems, and aggressive behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(22 reference statements)
2
2
0
Order By: Relevance
“…Different health-related risky behaviors were related to their general situation, quality of life, intelligence level or core symptoms. These results were consistent with the results of previous studies[ 8 , 29 - 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…Different health-related risky behaviors were related to their general situation, quality of life, intelligence level or core symptoms. These results were consistent with the results of previous studies[ 8 , 29 - 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…We are the first to study reciprocal associations between autistic-like features and FSS during adolescence using a longitudinal design. The stable association that we found between autistic-like features and FSS is an extension of previous cross-sectional studies that showed elevated FSS in autistic adolescents compared to non-autistic peers (Paul et al, 2015;Schroeder et al, 2011). It is also in line with the finding that school-aged children with more severe autistic-like features exhibit higher levels of FSS compared to those with autistic-like features of a lower severity (Kim et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In preschoolers, a relation between ASD and somatic symptoms was found that remained significant after removing the items concerning gastrointestinal complaints (Fulceri et al, 2016). Other studies reported a significantly higher aggregate of somatic symptoms in autistic children compared to non-autistic peers (Bos et al, 2018;Paul et al, 2015). Another study found higher levels of autistic-like features in a clinical sample of children and adolescents with chronic pain, compared to the general population (Lipsker et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…The Child Behaviour Checklist [29] is a parent/carer-completed scale and reports the activities, behaviours and functioning of the young person as previously described in more detail in Paul et al [30]. The caregiver scores each item 0 if it is “not true”, 1 if it “sometimes or somewhat true” and 2 if it is “very true or often true” of the child.…”
Section: Methodsmentioning
confidence: 99%